2005
DOI: 10.1103/physrevb.72.075420
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and III-V compound nanotubes: Structural and electronic properties

Abstract: Unusual physical properties of single-wall carbon nanotubes have started a search for similar tubular structures of other elements. In this paper, we present a theoretical analysis of single-wall nanotubes of silicon and group III-V compounds. Starting from precursor graphene-like structures we investigated the stability, energetics and electronic structure of zigzag and armchair tubes using first-principles pseudopotential plane wave method and finite temperature ab-initio molecular dynamics calculations. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
208
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(219 citation statements)
references
References 71 publications
6
208
0
1
Order By: Relevance
“…Meanwhile, important optoelectronic applications [1] of 3D wz-GaN and wz-AlN rendered the synthesis of 2D SL AlN and GaN a priority study. Eight years after its first prediction [4], Tsipas et al [28] have demonstrated the epitaxial growth of ultrathin hexagonal h-AlN on Ag(111) substrate. More recently, Balushi et al [29] achieved the growth of one-to two-layer 2D h-GaN on SiC(0001) surface via graphene encapsulation method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, important optoelectronic applications [1] of 3D wz-GaN and wz-AlN rendered the synthesis of 2D SL AlN and GaN a priority study. Eight years after its first prediction [4], Tsipas et al [28] have demonstrated the epitaxial growth of ultrathin hexagonal h-AlN on Ag(111) substrate. More recently, Balushi et al [29] achieved the growth of one-to two-layer 2D h-GaN on SiC(0001) surface via graphene encapsulation method.…”
Section: Introductionmentioning
confidence: 99%
“…After the synthesis of graphene [3], questions have been raised as to whether group IV elemental and group III-V compound semiconductors can form stable single-layer (SL) graphenelike structures, despite the fact that they do not have layered structures like graphite. As early as in 2005, theoretical studies based on the total energy minimization have shown that, in fact silicon, GaN, GaAs, and AlN can form stable, SL structures in honeycomb structure with twodimensional (2D) hexagonal (h) lattice [4]. Motivated with this result, extensive studies based on ab initio density functional theory (DFT) calculations of total energy, phonon, and finitetemperature molecular dynamics calculations demonstrated that SL silicene [4,5], germanene [5], group IV-IV and III-V compounds [4,[6][7][8], as well as group II-VI compounds like ZnO [9], can form stable, free-standing, SL structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Jang et al 56 have investigated magnetic properties of Fe-, Co-and Ni-doped infinite silicon nanotubes with hexagonal prism structure for two different numbers of dopants. Likewise, Durgun et al 21 have explored whether various structures doped with TM atoms in the pursuit of finding the energetically most favorable units can be generated by stacking of triangle, pentagons, or hexagons of Si.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, contact metals might account as an alternative to traditional doped source-drain device structures where one suffers from fundamental problems such as high leakage current and parasitic resistance arise from the sub-100 nm range scaling. On the contrary, silicon nanowire, 17 or nanotube [18][19][20][21][22] itself might be incorporated as nanocontact structure. Although the stability of various silicon nanotubes ͑SiNTs͒ has been verified from computational studies, [18][19][20][21][22] and energetics of SiNTs, for example dependence of strain energy on the tube diameter and chirality, is studied in detail, 23 it is very difficult to realize them experimentally because of sp 3 hybridization tendency of silicon in SiNTs.…”
Section: Introductionmentioning
confidence: 99%